Linguística e topologia em Jacques Lacan : princípios de uma continuidade epistemológica na formalização do sujeito - Márcio Heber Andrade Mendonça (2021)
This research proposes to verify the hypothesis that there is a continuity between the fields of Linguistics and Topology through the formalization of the concept of subject made by the French psychoanalyst Jacques Lacan. For this, we initially investigated how Lacan uses the structural linguistics founded by Ferdinand de Saussure, subverting it, in order to propose a reinterpretation of psychoanalysis from the significant logic. Going through the properties of this logic, we see that one of its fundamental conditions is the differential relationship between the elements that structure it: the signifiers themselves. These elements, which are the basis of Lacan's resumption of the Freudian program to show the importance of speech and language in psychoanalysis, are essentially articulated in a spatial way, as, for example, in the mechanisms of metaphor and metonymy. Going specifically into Lacan's articulations with topology, we verify how some principles of this epistemology are already present since the initial contact with the structural movement. When proposing his idea of structure and, as an effect, the subject, Lacan finds himself influenced by mathematics to expose models of a logic that recognizes in itself limits, holes and deformations related to those also presented as part of clinical practice. Among these models, we elected the Moebius Band to investigate the consequences of this epistemological articulation with regard to the analytical act. We conclude our hypothesis in an affirmative way, since the structure of the subject, as proposed by Lacan, using linguistics, requires to be thought also from a topological perspective, once its disposition to spatial deformations is noticed - exemplarily employed also in the artistic field.